Microbubble-Based Sonothrombolysis Using a Planar Rectangular Ultrasonic Transducer - Papadopoulos, Nicos G.; Damianou, Christakis A. (My University, 2017)
The aim of the proposed study was to evaluate in an in vitro flow model the ability of small planar rectangular (2 × 10 mm2) ultrasonic transducer to enhance thrombolysis induced by the thrombolytic agent tenecteplase (TNK-tPA). Methods To provide a more realistic clinical environment of stroke, the study was conducted under realistic flow conditions and TNK-tPA concentrations. Fully retracted porcine blood clots were used to determine the thrombolytic efficacy of ultrasound (US) waves as an adjunct to TNK-tPA or in combination with microbubbles (MBs). Two ultrasonic flat rectangular transducers were used in the experiments, operating at 3.7 and 5.2 MHz respectively. A pulsed US protocol that maintained temperature elevation at the target of 1°C was applied. Thrombolysis efficacy was measured in milligrams of mass clot removed. Results The effect of experimental parameters, such as power, frequency, and MBs administration, on thrombolysis efficacy was explored. Conclusions The results revealed that thrombolysis efficacy decreases at higher frequency, and therefore, the possibility of using lower frequency to improve efficacy should be further investigated. Additionally, study findings demonstrated that the combination of 3.7 MHz with MBs as an adjunct to TNK-tPA strongly enhanced thrombolysis efficacy, because with 30 minutes of treatment, 700 mg of clot was removed through nonthermal mechanisms. As a final point, this study has shown that MBs dose influences thrombolysis enhancement, because higher thrombolytic efficacy was observed with higher doses of MBs.
Keywords: intravascular; stroke; thrombus ultrasound; TNK-tPA